A review of granulocyte colony-stimulating factor receptor signaling and regulation with implications for cancer - Park, Sungjin David; Saunders, Apryl S.; Reidy, Megan A.; Bender, Dawn E.; Clifton, Shari; Morris, Katherine T. (Frontiers in Oncology, 2022)
Granulocyte colony-stimulating factor receptor (GCSFR) is a critical regulator of granulopoiesis. Studies have shown significant upregulation of GCSFR in a variety of cancers and cell types and have recognized GCSFR as a cytokine receptor capable of influencing both myeloid and non-myeloid immune cells, supporting pro-tumoral actions. This systematic review aims to summarize the available literature examining the mechanisms that control GCSFR signaling, regulation, and surface expression with emphasis on how these mechanisms may be dysregulated in cancer. Experiments with different cancer cell lines from breast cancer, bladder cancer, glioma, and neuroblastoma are used to review the biological function and underlying mechanisms of increased GCSFR expression with emphasis on actions related to tumor proliferation, migration, and metastasis, primarily acting through the JAK/STAT pathway. Evidence is also presented that demonstrates a differential physiological response to aberrant GCSFR signal transduction in different organs. The lifecycle of the receptor is also reviewed to support future work defining how this signaling axis becomes dysregulated in malignancies.